Visual functions in non-overlapping visual field defects: dichoptic experiments in healthy subjects with simulated scotomas - Gazanchian, Mehrdad; Cornelissen, Frans W.; Jansonius, Nomdo M. (Vision research (Oxford), 2025)
In clinical care, glaucoma patients are often assumed to have normal vision as long as each point of visual space is seen normally by at least one eye. Recent studies have challenged this assumption. In glaucoma, visual perception of spatially fragmented binocular input may be altered by long-term neural adaptation and by acute sensory effects. These two components cannot be disentangled easily in glaucoma patients, but the latter component can be isolated with simulated visual field defects in healthy subjects. Therefore, the aim of this study was to find out if simulated non-overlapping visual field defects (NOVFDs) can hamper certain aspects of visual perception in healthy subjects. We included 10 healthy subjects in this cross-sectional, observational study. Subjects underwent psychophysical experiments targeting contrast sensitivity, motion perception (line motion and coherent dot motion), and shape recognition. Experiments were done in three different viewing conditions using a stereoscope: (1) binocularly, (2) with simulated NOVFDs, and (3) monocularly. The NOVFDs viewing condition resulted in a decreased performance across all tested aspects of visual perception, when compared to the binocular viewing condition. The NOVFDs viewing condition resulted in a poorer performance in shape recognition compared to the monocular viewing condition. No other differences were observed between these two viewing conditions. Our results show that simulated NOVFDs impair certain visual functions. This contributes to the basic understanding of visual perception in healthy subjects and acts as a first step in the understanding of the relationship between disease stage and the visual problems that glaucoma patients may experience.